"Walking on eggshells": traversing the emotional and meaning making processes surrounding hurtful course evaluations. Issue 3 (3rd July 2019) - Carmack, Heather J.; LeFebvre, Leah E.
ABSTRACT: Instructors often struggle with how to make sense of and handle hurtful student course evaluation comments. These comments can be difficult to resolve when they move from constructive course criticisms to hurtful comments about an instructor's race, gender, appearance, or personality. Relying on the Meaning Making Model (MMM), this study explored the emotional and sense-making processes surrounding hurtful evaluation comments. Participants ( N = 90) described how they made sense of their hurtful student course evaluation comments. Findings revealed that instructors primarily experienced rage, sadness, neglect, and suffering, and engaged in a meaning making process characterized by self-doubt and subsequent negative emotional spiraling. Hurtful course evaluation comments influenced how instructors perceived course evaluations, their student–instructor relationships, and their effort to communicate with students. Participants also identified preventative measures to avoid future hurtful comments. Implications offer extensions to the MMM and practical recommendations for instructors.